Design and synthesis of a push–pull arylene–vinylene terpyridyl conjugate: multifunctional behaviors exhibited by a single molecule. Issue 13 (8th June 2022) - Sil, Amit; Ghosh, Utsav; Dolai, Suman; Manna, Soumitra; Maity, Apurba; Patra, Sanjib K.
Abstract : All-round performance: a donor–π–acceptor type push–pull arylene–vinylene conjugated terpyridine showing multifunctional properties of solvatochromism, vapochromism, piezofluorochromism and remarkable fluorescence sensing properties. Abstract : A multifunctional D–π–A push–pull arylene–vinylene conjugated terpyridine, 4′-(4-{2-[4-[bis(4-thiophen-2-yl-phenyl)amino]phenyl-ethenyl]}phenyl)-2, 2′:6′, 2′′-terpyridine, has been designed and successfully developed. Its photophysical properties were systematically explored, revealing its tunable multifunctional behaviors including solvatochromism, vapochromism, piezofluorochromism and remarkable chemosensing properties. The push–pull congener exhibits strong emission which is highly sensitive to solvent polarity, showing blue to yellow fluorescence in the presence of volatile organic compounds (VOCs). The compound also exhibits reversible mechanochromic behavior with high color contrast between yellow and green in its pristine and ground form. Moreover, the synthesized push–pull probe shows remarkable sensitivity towards NACs at the ppb level (especially for picric acid) in solution, vapor and contact mode as a 'turn-off' sensor which can be visualized by the naked eye. The fluorescence quenching through supramolecular complexation has been further supported by DFT calculations, time-resolved fluorescence and 1 H NMR titration. Furthermore, the conjugated terpyridine can efficiently detect toxic Hg 2+ at the submicromolar level with high selectivity and sensitivity without interference by other competing metal ions. The selectivity, sensitivity, reversibility, and recyclability allowed us to demonstrate its practical utility as a solid state kit for onsite detection of toxic Hg 2+, NACs and volatile organic solvents.